Effect of Physiotherapy on Pain and Recovery of Physical Function after Total Knee Arthroplasty: One Month Follow-up - Alghadir, A.; Iqbal, Z. A.; Anwer, S. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2016)
Objective: To investigate the effect of physiotherapy on pain and recovery of physical function after total knee arthroplasty (TKA).Methods: 80 patients (male 29, female 51) in the age group of 48–80 years (mean 63.28, SD 9.44) undergone TKA (bilateral 50, unilateral 30) participated in the prospective interventional study. All the participants received daily inpatient physiotherapy and outpatient physiotherapy sessions 4 days a week for 3 weeks. Pain and physical function were assessed at preoperatively, 1 week, and 1 month post-operatively by visual analogue scale (VAS) and lower extremity functional scale (LEFS), respectively. The data was analysed using repeated measures analysis of variance.Results: VAS score at 1-week after surgery was 4.38 (SD 0.99) vs. 2.13 (SD 1.35) at 1-month (p<0.001). At 1-month the VAS score was 2.13 (SD 1.35) vs. 8.85 (SD 0.99) preoperatively (p<0.001). LEFS at 1-week after surgery was 29.19 (SD 11.94) vs. 55.99 (SD 14.95) at 1-month (p<0.001). At 1-month the functional score was 55.99 (SD 14.95) vs. 17.26 (SD 9.70) preoperatively (p<0.001).Conclusions: A regime of physical therapy program provides early pain reduction and improvement of function after TKA at 1-month post-operatively.
Keywords: early rehabilitation; osteoarthritis; pain; physiotherapy; functional independence